LAWAS SAKECO: MENGGALI NILAI-NILAI ETNOPEDAGOGIK DALAM PEMBELAJARAN SOSIOLOGI - El Hawa, Esa; Wildan, Dadan; Komariah, Siti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This article explains that lawas sakeco serves as a source for learning sociology. The aim of this research is to explore the meanings within lawas sakeco, which is rich in social values, to enhance the study of sociology. This research is descriptive in nature. The objects of the research are lawas sakeco and ethnopedagogical studies. Data collection is conducted through library research. The technique for data analysis involves examining the values contained within lawas sakeco so that it becomes a resource for sociology learning. This research shows that (1) lawas sakeco is an oral tradition of folk poetry in the Samawa community, (2) lawas sakeco contains social values, and (3) lawas sakeco serves as a learning resource through the cultural wisdom of local traditions in sociology education.